Prevalence and risk factors associated with Maedi-Visna infection in sheep in the State of Maranhão, Brazil (Research, Society and Development, 2021)
In order to determine Maedi-Visna virus (MVV) seroprevalence and risk factors associated with infection in sheep, 445 animals of both sexes and different ages were tested using the Agarose Gel Immunodiffusion technique (IDGA). The animals were divided into two groups: group 1 composed of exhibition animals (n=70) and group 2 composed of animals from properties from the north, east and central mesoregions of the state of Maranhão (n=375). The general prevalence of MVV infection was 2.02%; 1.42% in group 1 and 2.13% in group 2. In the north mesoregion the prevalence was 2.20%, while a total of 40% of the animals living in municipalities for MVV. It was observed that 1.15% of males and 2.23% of females were seropositive (p> 0.20). Regarding breeds, the Dorper (1.66%); Santa Inês (1.67%); White Dorper (33.33%) and Texel (4.34%) were the most affected. This was the only variable among all the risk factors studied that had a significant association in multivariate analysis (p